Variation in ambulance call rates for care homes in Torbay, UK. (31st August 2016) - Hancock, Jason; Matthews, Justin; Ukoumunne, Obioha C.; Lang, Iain; Somerfield, David; Wenman, James; Dickens, Chris
Abstract: Emergency ambulance calls represent one of the routes of emergency hospital admissions from care homes. We aimed to describe the pattern of ambulance call rates from care homes and identify factors predicting those homes calling for an ambulance most frequently. We obtained data from South Western Ambulance Service NHS Foundation Trust on 3138 ambulance calls relating to people aged 65 and over from care homes in the Torbay region between 1 April 2012 and 31 July 2013. We supplemented this with data from the Care Quality Commission (CQC) website on home characteristics and outcomes of CQC inspections. We used descriptive statistics to identify variation in ambulance call rates for residential and nursing homes and fitted negative binomial regression models to determine if call rates were predicted by home type (nursing versus residential), the five standards in the CQC reports, dementia care status or travel time to hospital. One hundred and forty‐six homes (119 residential and 27 nursing) were included in the analysis. The number of calls made ranged from 1 to 99. The median number (IQR; range) of calls per resident per year was 0.51 (0.21–0.89; 0.03–2.45). Nursing homes had a lower call rate than residential homes [adjusted rate ratio (ARR) 0.29; 95% CI: 0.22–0.40; P  < 0.001]; care homes failing the quality and suitability of management standard had a lower call rate compared to those who passed (ARR 0.67; 95% CI: 0.50–0.90; P  = 0.006); and homes specialising in dementia had a higher call rate compared to those not specialising (ARR 1.56; 95% CI: 1.23–1.96; P  < 0.001). These findings require replication in other regions to establish their generalisability and further investigation is required to determine the extent to which call rate variability reflects the different needs of resident populations or differences in care home policies and practice.